Surface Functionalization of Black Phosphorus via Amine Compounds and Its Impacts on the Flame Retardancy and Thermal Decomposition Behaviors of Epoxy Resin - Shaoling Lin (MDPI AG, 2021)
Recently, lots of effort has been placed into stabilizing black phosphorus (BP) in the air to improve its compatibility with polymers. Herein, BP was chemically functionalized by aliphatic amine (DETA), aromatic amine (PPDA) and cyclamine (Pid) via a nucleophilic substitution reaction, aiming to develop an intensively reactive BP flame retardant for epoxy resin (EP). The -NH2 group on BP-DETA, BP-PPDA and BP-Pid reacted with the epoxide group at different temperatures. The lowest temperature was about 150 °C for BP-DETA. The impacts of three BP-NH2 were compared on the flame retardancy and thermal decomposition of EP. At 5 wt% loading, EP/BP-NH2 all passed UL 94 V 0 rating. The limiting oxygen index (LOI) of EP/BP-PPDA was as high as 32.3%. The heat release rate (HRR) of EP/BP-DETA greatly decreased by 46% and char residue increased by 73.8%, whereas HRR of EP/BP-Pid decreased by 11.5% and char residue increased by 50.8%, compared with EP. Average effective heat of combustion (av-EHC) of EP/BP-Pid was lower than that of EP/BP-DETA and EP/BP-PPDA. In view of the flame-retardant mechanism, BP nanosheets functionalized with aliphatic amine and aromatic amine played a dominant role in the condensed phase, while BP functionalized with cyclamine was more effective in the gas phase.